FIKIH BARU JAMAL AL-BANNA: KRITIK TERHADAP TERTUTUPNYA PINTU IJTIHAD - Zainal Arifin; Mohammad Fauzan Ni'ami; Noor Rizqiya Fimaulidina (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This research is motivated by the doctrine of the closed door of ijtihad. The implication is that around the 19th century figures emerged who constructively criticized this doctrine. The reason the researcher chose Jamal al-Banna was because he was one of the reformers of Islamic law who tried to reconstruct Islamic law with the paradigm of reason and freedom of authenticity (al-Bara'ah al-Ashliyyah). This article tries to examine further how the stagnation of critical doctrine carried out by Jamal al-Banna and how coercion resulted from this criticism. This article finds that there is a structuralist essence in Jamal al-Banna's critique of ijtihad. The door to Ijtihad is not closed as long as humans have reason. Therefore, reason is the initial foundation in efforts to formulate the fiqh Jadid which was initiated by Jamal al-Banna.